Symmetry-based approach to oligostilbenoids: Rapid entry to viniferifuran, shoreaphenol, malibatol A, and diptoindonesin G - Jung, Youngeun; Singh, Dileep Kumar; Kim, Ikyon (Beilstein Journal of Organic Chemistry, 2016)
The recognition of the local symmetric image within benzofuran-based natural oligostilbenoids guided us to design a modular synthetic approach to these molecules by utilizing a three-step sequence consisting of Sonogashira coupling, iodocyclization, and Suzuki coupling. During our synthesis, the relative reactivities of ester, aldehyde, and alkoxy groups on the same aryl ring toward the neighboring alkyne in the iodine-mediated cyclization reactions were explored. Starting from the symmetrical 3,5-dimethoxybenzyl alcohol, this route allowed rapid access to 2,3-diarylbenzofuran, a key intermediate to several oligostilbenoid natural products, in good overall yields.
Keywords: anticancer agent; iodocyclization; natural product; oligostilbenoids; Pd-catalyzed coupling